2021
DOI: 10.1021/acsami.1c14088
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Antibacterial and Conductive Hydrogels Based on the Distinct Bactericidal Effect of Polyaniline for Infected Chronic Wound Healing

Abstract: Most chronic wounds suffer from infections, and their treatment is challenging. The usage of antibiotics may lead to bacterial resistance and adverse side effects. Positively charged substances have shown promise, but their applications are usually limited by certain cytotoxicity or complex synthesis. Doped polyaniline that carries a high density of positive charges would be a promising candidate due to its good biocompatibility and easy availability, but its interaction with bacteria has not been elucidated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…application in vascular tissue engineering (Yu et al, 2020). Wu et al (2021) used polyaniline and sulfonated hyaluronic acid to construct flexible hydrogels with simulated skin conductivity. In vivo results showed that the electrical stimulation method by this hydrogel was superior to the present clinical electrical stimulation strategy to promote the healing of infected chronic wounds.…”
Section: Hyaluronic Acid Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…application in vascular tissue engineering (Yu et al, 2020). Wu et al (2021) used polyaniline and sulfonated hyaluronic acid to construct flexible hydrogels with simulated skin conductivity. In vivo results showed that the electrical stimulation method by this hydrogel was superior to the present clinical electrical stimulation strategy to promote the healing of infected chronic wounds.…”
Section: Hyaluronic Acid Hydrogelsmentioning
confidence: 99%
“…Data showed that HA with a higher sulfonation degree had stronger functions of inhibiting inflammatory macrophages, promoting the adhesion, proliferation, and migration of EC and regulating and maintaining the contractile phenotype of SMCs ( Yu et al, 2020 ), which is a promising potential application in vascular tissue engineering ( Yu et al, 2020 ). Wu et al (2021) used polyaniline and sulfonated hyaluronic acid to construct flexible hydrogels with simulated skin conductivity. In vivo results showed that the electrical stimulation method by this hydrogel was superior to the present clinical electrical stimulation strategy to promote the healing of infected chronic wounds.…”
Section: Biomaterials Prepared With Hyaluronic Acidmentioning
confidence: 99%
“…23 Professor Wang's group developed a series of conductive hydrogels for chronic wound treatment. [96][97][98][99] For example, they initiated the polymerization of aniline monomers in situ in polyacrylamide hydrogels to construct a novel conductive hydrogel dressing. 96 They found that sulfonated HA-doped polyaniline with a high density of positive charges could specifically interact with lipoteichoic acid to disrupt Gram-positive bacterial cell walls.…”
Section: Hydrogelsmentioning
confidence: 99%
“…However, most hydrogels lack conductivity due to the insulating properties of conventional polymer networks. Commonly used methods to enhance the conductivity of hydrogel include filling conductive fillers (graphene [ 17 , 18 ], carbon nanotubes [ 19 , 20 ], polypyrrole [ 21 , 22 ] and polyaniline [ 23 ], etc.) or adding soluble electrolytes (e.g., LiCl, NaCl, and (NH 4 ) 2 SO 4 ) [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%